1999
DOI: 10.1111/1467-8624.00010
|View full text |Cite
|
Sign up to set email alerts
|

Children's Judgments of Flags and Flag‐Burning

Abstract: This study examined children's conceptions of flags as social conventions and understandings of the symbolic and psychological consequences associated with transgressions toward flags. Seventy-two children, at 6, 8, and 10 years, answered general questions about flags as social conventions and judged flag-burning scenarios in which intentions of agents and consequences for recipients were varied. Flag-burning acts were motivated by symbolic, accidental, or instrumental intentions and occurred in public or priv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 22 publications
1
19
0
1
Order By: Relevance
“…Wainryb and colleagues (Wainryb, Shaw, Laupa, & Smith, 2001;Wainryb, Shaw, & Maianu, 1998) found that children exhibit increasing tolerance for some forms of dissent in belief and expression with age (although not dissent on moral values and beliefs). Similarly, Helwig and Prencipe (1999) found that although both younger and older children tend to view antipatriotic sentiment expressed in acts of flag burning as wrong, children were less likely with age to advocate laws that prohibit flag burning, reflecting their concern with censorship of the expression of unpopular beliefs. Given the paucity of research on nonmoral character values in the social-cognitive development literature, it was not possible to make specific predications about this area, except to say that although children may endorse the teaching of relevant nonmoral character values (such as "industriousness") in school settings, they may be less likely to view them as obligatory by law or to see them as necessary candidates for values education than they would moral values (Nucci, 1997).…”
Section: Introductionmentioning
confidence: 98%
“…Wainryb and colleagues (Wainryb, Shaw, Laupa, & Smith, 2001;Wainryb, Shaw, & Maianu, 1998) found that children exhibit increasing tolerance for some forms of dissent in belief and expression with age (although not dissent on moral values and beliefs). Similarly, Helwig and Prencipe (1999) found that although both younger and older children tend to view antipatriotic sentiment expressed in acts of flag burning as wrong, children were less likely with age to advocate laws that prohibit flag burning, reflecting their concern with censorship of the expression of unpopular beliefs. Given the paucity of research on nonmoral character values in the social-cognitive development literature, it was not possible to make specific predications about this area, except to say that although children may endorse the teaching of relevant nonmoral character values (such as "industriousness") in school settings, they may be less likely to view them as obligatory by law or to see them as necessary candidates for values education than they would moral values (Nucci, 1997).…”
Section: Introductionmentioning
confidence: 98%
“…Second, outside of work in cultural psychology there is some precedent for 'moral' judgements of distinctly symbolic matters. Studies have shown that judgements of damage to objects (e.g., flag-burning) are moralised (Helwig & Prencipe, 1999) and that certain sacred values reflect non-instrumental reasoning (Ginges & Atran, 2009). Lastly, the distinction may underlie group differences in moral points of view.…”
Section: Discussionmentioning
confidence: 99%
“…Second, psychologists (e.g., Turiel, 1983) explain our abilities to perceive moral violations as inferential reasoning processes facilitated by observing and/or experiencing the intrinsic or instrumental consequences of acts (recognition of pain, unequal distribution, etc). Symbolic meanings have been Reasoning about family honour 81 largely absent in studies of moral psychology (although for an exception regarding judgements of flag-burning, see Helwig & Prencipe, 1999). As highlighted above, family honour is often upheld through acts of premarital sexual abstinence and decisions about suitable marriage partners.…”
Section: Family Honour As a Moral Psychological Phenomenonmentioning
confidence: 99%
See 2 more Smart Citations